2008
DOI: 10.5012/bkcs.2008.29.5.1025
|View full text |Cite
|
Sign up to set email alerts
|

Effective Amidation of Carboxylic Acids Using (4,5-Dichloro-6-oxo-6H-pyridazin-1-yl)phosphoric Acid Diethyl Ester

Abstract: (4,5-Dichloro-6-oxo-6H-pyridazin-1-yl)phosphoric acid diethyl ester (3a) are efficient and selective coupling agents for the amidation of carboxylic acids. Amidation of aliphatic and aromatic carboxylic acids with aliphatic and aromatic amines using 3a under mild condition gave chemoselectively the corresponding amides in good to excellent yield. Three protected-dipeptides were also synthesized from N-BOC-Phe and O-Meamino acid hydrochlorides using 3a under mild condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Because the esterification occurs via acyl phosphate as a key intermediate, this is more effective than the method using 4,5-dichloro-2-[4-nitrobenzenesulfonyl]-pyridazin-3­(2 H )-one ( 5 ) as a coupling agent. Kang et al demonstrated the amidation of carboxylic acids with amines using phosphoric acid diethyl ester 10 . The amidation of aliphatic and aromatic carboxylic acids with amines using 10 in the presence of potassium carbonate in THF at room temperature affords chemoselectively the corresponding amides in good to excellent yields (Scheme b).…”
Section: Pyridazin-3(2h)-ones As Recyclable Functional Group Carriersmentioning
confidence: 99%
“…Because the esterification occurs via acyl phosphate as a key intermediate, this is more effective than the method using 4,5-dichloro-2-[4-nitrobenzenesulfonyl]-pyridazin-3­(2 H )-one ( 5 ) as a coupling agent. Kang et al demonstrated the amidation of carboxylic acids with amines using phosphoric acid diethyl ester 10 . The amidation of aliphatic and aromatic carboxylic acids with amines using 10 in the presence of potassium carbonate in THF at room temperature affords chemoselectively the corresponding amides in good to excellent yields (Scheme b).…”
Section: Pyridazin-3(2h)-ones As Recyclable Functional Group Carriersmentioning
confidence: 99%